PERBANDINGAN PENGAPLIKASIAN CONCEALER DAN FOUNDATION PADA RIAS WAJAH MALAM HARI TERHADAP KOREKSI BENTUK ALIS TEBAL - DUI VIVI WAHYUNI (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
The purpose of this study was to determine the results of thick eyebrow formation without shaving eyebrows by applying cream concealer and foundation cream to night makeup, to find out the best results and the panelists' favorite response. This research method is quasi-experimental method with a Non equivalent control group design. The population in the study were students of the Makeup and Beauty of the Padang State University University who had the shape of thick eyebrows and long face shapes. Sampling using purposive sampling technique and using t test analysis. The results of the analysis show that there are significant differences in the results of the resembling indicator of obtaining p>0.05 (P = 0.635), the highest average in the experimental group (X2) is 3.40, at the level of smoothness p<0.05 (p = 0.020), The highest average score in the experimental group (X2) is 3.60, at the level of fineness p<0.05 (p = 0.047), the highest average value is obtained by the experimental group (X2) is 3.47. the best comparison of results is to apply foundation cream (X2). The results show that the advantages of foundation cream are easier to use and are disguised in night makeup